“¿Triste estás? I don’t know nan molla”: Multilingual pop song fandubs by @miree_music - Zhang, Leticia Tian; Vazquez-Calvo, Boris (My University, 2022)
Fandubbing, or dubbing made by fans of any audiovisual product, is a lin- guistically and technologically sophisticated enterprise enacted by many devoted fans. This study presents the case of Miree, a 24-year-old fandubber with more than 1 million subscribers on YouTube and more than 300 multi- lingual fandubbed songs. Using a qualitative-interpretive approach, we con- ducted an in-depth interview with Miree and analyzed her top 30 videos by views to reveal how Miree performed fandubbing, how she expressed her fan identity through fandubbing, and which were some of the implications of fandubbing for language learning. Results show that Miree realized both interlinguistic genuine fandubbing and intralinguistic parodic fandubbing, strategically adopting translanguaging to orchestrate a multimodal perfor- mance, engage her fanbase, and activate several informal language learning opportunities and contexts afforded by fandubbing.
Keywords: Lenguas - Estudio y enseñanza; Identidad; fandub; dubbing; fan translation; informal language learning; translanguaging